Learning from Errors: How Error Analysis Enhances English Proficiency in Sekolah Tinggi Pariwisata Mataram - Suputra, I Gede Widya (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the effectiveness of applying error analysis in improving English writing skills for tourism among Diploma 3 Hospitality students at the Mataram Tourism College, Lombok. This study uses an English for Specific Purposes (ESP) approach with a descriptive-analytical design and learning intervention. Data were obtained from the creative writing assignments of fifth-semester students, which were analysed to identify the types and frequency of language errors, particularly in terms of grammar. The results of the analysis showed that the most dominant errors were errors in the use of verb tenses, especially the present tense and past tense, with developmental errors occurring more frequently than errors due to interference from the first language. Based on these findings, remedial learning was provided, focusing on the types of errors with the highest frequency. The results of the evaluation after the intervention showed a significant improvement in the accuracy of tense usage in students' writing. These findings indicate that error analysis is an effective and data-driven approach to improving English writing skills for tourism and supports more targeted learning planning.